FACTORS INFLUENCING LABOUR PRODUCTIVITY OF INDONESIAN PUBLIC SECTOR WORKERS - Achmad Supriyanto (Graduate School of Universitas Negeri Malang, 2017)
This study aims to determine the influences of education level, salary, and age to the work productivity of public sector workers. This study uses descriptive correlational regression design. The populations of the data, consists of lecturers and administrative public sector workers. The population numbers exceed 1,542 and 25% of the sample is taken proportionally with stratified random sampling and as the result, obtaining 377 people as the data. The type of data is in the form of secondary data. The data analysis is using descriptive and multiple regression techniques. The results show that the levels of education, salary, and age have significant effect to the work productivity of the public sector workers.